Genetic and Environmental Factors Influencing Glutathione Homeostasis in Saccharomyces cerevisiae - Perrone, Gabriel G. (The American Society for Cell Biology, 2005)
Glutathione is an essential metabolite protecting cells against oxidative stress and aging. Here, we show that endogenously synthesized glutathione undergoes intercellular cycling during growth to stationary phase. Genome-wide screening identified ∼270 yeast deletion mutants that overexcrete glutathione, predominantly in the reduced form, and identified a surprising set of functions important for glutathione homeostasis. The highest excretors were affected in late endosome/vacuolar functions. Other functions identified included nitrogen/carbon source signaling, mitochondrial electron transport, ubiquitin/proteasomal processes, transcriptional regulation, ion transport and the cellular integrity pathway. For many mutants the availability of branched chain amino acids and extracellular pH influenced both glutathione homeostasis and cell viability. For all mutants tested, the onset of glutathione excretion occurred when intracellular concentration exceeded the maximal level found in the parental strain; however, in some mutants prolonged excretion led to substantial depletion of intracellular glutathione. These results significantly contribute to understanding mechanisms affecting glutathione homeostasis in eukaryotes and may provide insight into the underlying cause of glutathione depletion in degenerative processes such as Parkinson's disease. The important implications of these data for use of the yeast deletion collection for the study of other phenomena also are discussed.